Knowledge, attitude and perception of second-hand smoke and factors promoting smoking in Malaysian adolescents - Zainol Abidin, Najihah; Zulkifli, Aziemah; Zainal Abidin, Emilia; Rasdi, Irniza; Syed Ismail, Sharifah Norkhadijah; Abdul Rahman, Anita; Hashim, Zailina; Semple, Sean (International Union Against Tuberculosis and Lung Disease, 2014)
To identify the relationship between knowledge, attitude and perception regarding environmental tobacco smoke (ETS) and smoking among Malaysian adolescents living in states with complete or partial smoke-free legislation (SFL). A total of 898 respondents aged 13–14 years were randomly selected from 21 secondary schools. The Malay version of the modified Global Youth Tobacco Survey questionnaire was used. Hierarchical logistic regression was performed in examining predictors of smoking attempt among adolescents. Participants exposed to ETS >5 h/day were more likely to have smoked compared to those exposed to ETS <1 h/day (OR 4.1, 95%CI 1.03–16.0). Living in a state with partial SFL was associated with a two-fold increase in self-reported smoking attempts (OR 1.95, 95%CI 1.10–3.43) compared to living in a state with complete SFL. Negative attitudes and perceptions towards smoking and ETS exposure were linked to lower smoking attempts in states with complete SFL. Adolescents with limited ETS exposure who lived in a state with complete SFL were less likely to attempt smoking compared to those exposed more regularly to ETS and living in a state with partial SFL. Preventing adolescents from becoming smokers is the key to reducing national prevalence rates in smoking. There is a need to implement comprehensive smoke-free legislation nationally across Malaysia.